The 650 Billion Bargain : the Case for Modest Growth in America's Defense Budget. - O'Hanlon, Michael E. (Marshall papers., 2016)
U.S. defense spending isn't excessive and, in fact, should continue to grow because it's both affordable and necessary in today's challenging world. The United States spends a lot of money on defense about 607 billion in the current fiscal year. But Brookings national security scholar Michael O'Hanlon argues that is roughly the right amount given the overall size of the national economy and continuing U.S. responsibilities around the world. If anything, he says spending should increase modestly under the next president, remaining near 3 percent of gross domestic product. Recommendations in this book.